Capturing Aesthetic Experiences With Installation Art: An Empirical Assessment of Emotion, Evaluations, and Mobile Eye Tracking in Olafur Eliasson’s “Baroque, Baroque!” - Pelowski, Matthew; Leder, Helmut; Mitschke, Vanessa; Specker, Eva; Gerger, Gernot; Tinio, Pablo P. L.; Vaporova, Elena; Bieg, Till; Husslein-Arco, Agnes (Frontiers in Psychology, 2018)
Installation art is one of the most important and provocative developments in the visual arts during the last half century and has become a key focus of artists and of contemporary museums. It is also seen as particularly challenging or even disliked by many viewers, and-due to its unique in situ, immersive setting-is equally regarded as difficult or even beyond the grasp of present methods in empirical aesthetic psychology. In this paper, we introduce an exploratory study with installation art, utilizing a collection of techniques to capture the eclectic, the embodied, and often the emotionally-charged viewing experience. We present results from an investigation of two pieces, both part of Olafur Eliasson's exhibition "Baroque, Baroque" held at the Belvedere museum in Vienna. These were assessed by administered pre- and post-viewing questionnaires focusing on emotion, meaning-making, and appraisals, in tandem with mobile eye tracking to consider viewers' attention to both installed artworks and/or the museum environment. The data showed differences in participants' emotional states, appraisals, and visual exploration, which together paint a picture of the aesthetic reactions to the works. These differences also showed how viewers' appraisal strategies, meaning making, and physical actions facilitated relatively more or less deep engagement with, and enjoyment of, the art pieces. The results are discussed in terms of their implications for museum studies, art education, and theory in empirical aesthetics.